Effect of processing method on the quality of cowpea(Vigna unguiculata) flour for akara preparation (2003)
Cow peas were prepared intoflour by wet dehulling, wet milling into paste and drying; wet dehulling, drying and milling; and wet dehulling, wet milling and foam mat drying. Proximate chemical composition and functional properties (water and fat absorption capacities, foaming capacity, foam stability, bulk density, gelation capacity and emulsification capacity) of flours and of paste prepared by wet dehulling, wet milling and no drying,were determined. Akara from fresh paste and pastes reconstituted from flour was organoleptically evaluated. Reconstituted paste of flour from ground dry cotyledons produced the best quality akara, compared with the control. Akara from reconstituted foam mat dried and ground dry paste flours were less acceptable.